A lithium-ion battery separator with a modified ceramic coating

By modifying the ceramic composite coating, the problem of high shrinkage and poor breathability of lithium-ion battery separators at high temperatures is solved, the electrolyte wetting and thermal stability are improved, and the lithium ion transmission and battery performance are improved.

CN118712663BActive Publication Date: 2024-12-17SHANGHAI YONGMING ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410914074.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2024-12-17
Estimated Expiration
2044-07-09

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of lithium ion battery separators, and discloses a lithium ion battery separator with a modified ceramic coating, comprising a base film and a modified ceramic coating, wherein the modified ceramic coating is arranged on at least one side surface of the base film, and the modified ceramic coating comprises the following raw materials in parts by weight: 40-70 parts of a modified ceramic composite material, 5-20 parts of a binder, and 0.5-5 parts of a dispersant; the modified ceramic composite material is a modified ceramic composite material prepared by coupling agent-modified nano-alumina grafted with carboxylated halloysite nanotubes and adsorbing dopamine. The invention adds the modified ceramic composite material to make the prepared separator have excellent electrolyte wettability, low heat shrinkage, good thermal stability, high air permeability, good tensile strength and ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery separators, and in particular relates to a lithium ion battery separator with a modified ceramic coating. Background Art

[0002] Lithium-ion batteries have the advantages of high specific energy, long cycle life, and no memory effect, and are widely used in many fields such as new energy vehicles, aerospace, and military industry. As an important component of lithium-ion batteries, the diaphragm plays an electronic insulation role between the positive and negative electrodes, while ensuring the free movement of ions. Although the diaphragm does not directly participate in the electrochemical reaction of the battery, its structure and performance play an important role in the battery cycle life, safety, energy density, and power density.

[0003] At present, commonly used diaphragms such as polyethylene diaphragms have problems such as low melting point (130°C), high shrinkage at high temperature, and poor wettability with electrolyte. The existing technology is considered to be an effective strategy with controllable cost and easy large-scale production by coating heat-resistant ceramic particles on the surface of polyethylene diaphragms. Among them, nano-alumina is an inorganic ceramic particle commonly used as a coating material for lithium-ion battery diaphragms. It has high thermal stability and chemical inertness, and has excellent high temperature resistance. It can greatly improve the safety of lithium-ion batteries. In addition, it can neutralize free HF in the electrolyte and increase the service life of the battery. The dense nano-alumina coating on the surface of the ceramic diaphragm can improve the wettability of the electrolyte, but the dense nano-alumina coating and the insulation of nano-alumina will affect the transmission of lithium ions, making the diaphragm permeability worse and the ion conductivity lower, affecting the battery performance. At the same time, the thermal stability of the diaphragm needs to be further improved. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a lithium-ion battery separator with a modified ceramic coating. By adding modified ceramic composite materials, the prepared separator has excellent electrolyte wettability, low thermal shrinkage, good thermal stability, high air permeability, good tensile strength and ionic conductivity.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A lithium-ion battery separator with a modified ceramic coating comprises a base film and a modified ceramic coating, wherein the modified ceramic coating is arranged on at least one side surface of the base film, and the modified ceramic coating comprises the following raw materials in parts by weight: 40 to 70 parts of a modified ceramic composite material, 5 to 20 parts of a binder, and 0.5 to 5 parts of a dispersant; the modified ceramic composite material is a modified ceramic composite material prepared by coupling agent-modified nano-alumina grafted with carboxylated halloysite nanotubes and adsorbing dopamine.

[0007] Preferably, the base film is one of a polypropylene base film, a polyethylene base film, and a polypropylene / polyethylene / polypropylene composite film; the binder is one or more combinations of polyvinyl alcohol, polyvinylidene fluoride, and polyacrylate; and the dispersant is one or more combinations of sodium carboxymethyl cellulose, polyacrylic acid, sodium polyacrylate, polyethylene glycol, and hydroxyethyl cellulose.

[0008] Preferably, the method for preparing the modified ceramic composite material comprises the following steps:

[0009] A. Take anhydrous ethanol and add 10wt% citric acid solution, adjust the pH to 3-4, add γ-glycidyloxypropyltrimethoxysilane and stir for 3-5 minutes, then let it stand for 0.5-1 hour and then add nano-alumina, stir at 75-90℃ for 1-5 hours, cool to room temperature, filter, wash, dry and grind to obtain coupling agent modified nano-alumina;

[0010] B. Take coupling agent-modified nano-alumina and carboxylated halloysite nanotubes, add N,N-dimethylformamide and perform ultrasonic treatment, then add triethylamine, place in an oil bath at 110-125°C and stir with nitrogen for 6-8 hours, wait for the reaction liquid to cool to room temperature, perform reduced pressure distillation, wash, filter and dry to obtain a ceramic composite material.

[0011] C. The ceramic composite material is dispersed in Tris-HCl buffer by ultrasonication, and then dopamine hydrochloride is added and stirred to react for 6 to 12 hours. After the reaction is completed, the modified ceramic composite material is obtained by centrifugation, filtration, washing and drying.

[0012] Preferably, in step A, the addition ratio of anhydrous ethanol, γ-glycidyloxypropyltrimethoxysilane and nano-alumina is 25 mL: 0.4-1.2 mL: 1-5 g.

[0013] Preferably, in step B, the mass ratio of the coupling agent-modified alumina to the carboxylated halloysite nanotubes is 1:0.4-0.8 g.

[0014] Preferably, in step C, the concentration of Tris-HCl buffer is 5-10 mmol / L, and the pH is 8.5; the mass ratio of the ceramic composite material to dopamine hydrochloride is 2-8:0.1-0.5.

[0015] Preferably, the method for preparing carboxylated halloysite nanotubes in step B comprises the following steps:

[0016] B1. Take γ-aminopropyltriethoxysilane, anhydrous ethanol and deionized water, stir and hydrolyze at room temperature for 1-2 hours, then add halloysite nanotubes and disperse them by ultrasonic, place under reflux reaction at 75-90°C for 12-24 hours, vacuum filter and dry after the reaction, and then use ethanol as solvent for Soxhlet extraction and dry again to obtain amination halloysite nanotubes;

[0017] B2. Take the aminated halloysite nanotubes and succinic anhydride, add N,N-dimethylformamide for ultrasonic dispersion, place at 25-50°C for stirring and reacting for 12-24 hours, vacuum filter and dry after the reaction is completed, and then dry after Soxhlet extraction with ethanol as solvent to obtain carboxylated halloysite nanotubes.

[0018] Preferably, in step B1, the addition ratio of γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and halloysite nanotubes is 8-15 mL: 90-180 mL: 25-45 mL: 2-5 g.

[0019] Preferably, in step B2, the mass ratio of the aminated halloysite nanotubes to succinic anhydride is 1-2.5:0.5-3.

[0020] Preferably, the method for preparing the lithium ion battery separator comprises the following steps:

[0021] (1) Weighing each raw material by weight, dissolving the binder in N-methylpyrrolidone, adding the modified ceramic composite material and the dispersant, mixing and dispersing the mixture in a ball mill, and obtaining a composite ceramic coating slurry;

[0022] (2) The composite ceramic coating slurry is coated on one side of the base film, dried and rolled up to prepare a lithium-ion battery separator.

[0023] Beneficial effects of the present invention:

[0024] The invention uses gamma-glycidyloxypropyltrimethoxysilane to modify nano-alumina, and a hydroxyl group at one end of the gamma-glycidyloxypropyltrimethoxysilane undergoes a condensation reaction with a hydroxyl group on the surface of the nano-alumina, thereby reducing the surface activity of the nano-alumina, avoiding agglomeration of the nano-alumina, and improving the uniformity of the nano-alumina in a ceramic coating slurry. At the same time, the invention uses gamma-aminopropyltriethoxysilane as a modifier to prepare amino-modified halloysite nanotubes, and then obtains carboxylated halloysite nanotubes by adding succinic anhydride. The epoxy group at the other end of the gamma-glycidyloxypropyltrimethoxysilane and the carboxyl group on the surface of the carboxylated halloysite nanotube undergo a ring-opening reaction, and the halloysite nanotubes are grafted onto the surface of the nano-alumina through the bridging effect of the gamma-glycidyloxypropyltrimethoxysilane to obtain a ceramic composite material. In addition, dopamine added can be oxidized and self-polymerized under alkaline conditions to form polydopamine, and the polydopamine has strong adhesion and can be adsorbed on the surface of the ceramic composite material to obtain a modified ceramic composite material.

[0025] The present invention utilizes modified ceramic composite materials to coat a base film to obtain a three-dimensional porous composite coating. The high aspect ratio halloysite nanotube tubular skeleton in the modified ceramic composite material can increase the gap between nano-alumina particles, which is helpful to construct a good gas transmission channel, improve the air permeability of the diaphragm, and is beneficial to the transmission of lithium ions and the storage and retention of electrolyte in the ceramic diaphragm, so that the wettability of the diaphragm electrolyte is improved. At the same time, the nano-alumina particles are grafted between the halloysite nanotube skeletons to ensure good heat resistance of the coating. The positive and negative charge surfaces inside and outside the halloysite nanotubes are beneficial to promoting the dissociation of lithium salts. The added dopamine is adsorbed on the surface of the halloysite nanotubes and forms a dense polydopamine layer through self-polymerization reaction. The abundant polar functional groups in the polydopamine layer, such as -NH2, C=O, -OH, etc., have extremely strong polar interaction forces with lithium ions, which can strengthen the affinity with the polar electrolyte, and are beneficial to forming a fast ion migration channel, promoting uniform transmission of lithium ions and dissociation of lithium salts, and improving the ionic conductivity of the diaphragm. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1 A method for preparing carboxylated halloysite nanotubes comprises the following steps:

[0028] B1, take 10mL of γ-aminopropyltriethoxysilane, 150mL of anhydrous ethanol and 30mL of deionized water, stir and hydrolyze at room temperature for 1h, then add 2g of halloysite nanotubes and disperse by ultrasonic, place under reflux reaction at 80°C for 24h, vacuum filter and dry after the reaction is completed, and then Soxhlet extraction with ethanol as solvent and dry again to obtain amination of halloysite nanotubes;

[0029] B2. Take 1g of amino-treated halloysite nanotubes and 0.5g of succinic anhydride, add 100mL of N,N-dimethylformamide for ultrasonic dispersion, place at 30°C for stirring and reacting for 24h. After the reaction is completed, vacuum filter and dry, and then use ethanol as solvent for Soxhlet extraction and dry again to obtain carboxylated halloysite nanotubes.

[0030] Example 2 A method for preparing a modified ceramic composite material comprises the following steps:

[0031] A. Take 25 mL of anhydrous ethanol and add 10 wt% citric acid solution to adjust the pH to 3, add 0.4 mL of γ-glycidyloxypropyltrimethoxysilane and stir for 3 min, then let stand for 0.5 h and add 2 g of nano-alumina, stir at 75 ° C for 1 h, cool to room temperature, filter, wash, dry and grind to obtain coupling agent modified nano-alumina;

[0032] B. Take 2 g of coupling agent-modified nano-alumina and 1 g of carboxylated halloysite nanotubes, add 100 mL of N,N-dimethylformamide and perform ultrasonic treatment, then add 3 mL of triethylamine, place in a 110°C oil bath and stir with nitrogen for 6 hours, wait for the reaction liquid to cool to room temperature, perform reduced pressure distillation, wash, filter and dry to obtain a ceramic composite material.

[0033] C. Take 2 g of the ceramic composite material and disperse it in 10 mmol / L Tris-HCl buffer by ultrasonic dispersion, then add 0.2 g of dopamine hydrochloride and stir to react for 8 hours. After the reaction is completed, centrifuge, filter, wash and dry to obtain a modified ceramic composite material.

[0034] Example 3 A lithium ion battery separator with a modified ceramic coating comprises a polyethylene-based film and a modified ceramic coating, wherein the modified ceramic coating comprises the following raw materials in parts by weight: 45 parts of a modified ceramic composite material, 7 parts of a binder polyvinylidene fluoride, and 0.5 parts of a dispersant sodium carboxymethyl cellulose;

[0035] The preparation method of the above-mentioned lithium ion battery separator comprises the following steps:

[0036] (1) Weighing each raw material by weight, dissolving the binder in N-methylpyrrolidone, adding the modified ceramic composite material and the dispersant, mixing and dispersing the mixture in a ball mill, and obtaining a composite ceramic coating slurry;

[0037] (2) The composite ceramic coating slurry is coated on one side of the polyethylene base film, dried and rolled up to prepare a lithium-ion battery separator.

[0038] Example 4 A lithium ion battery separator with a modified ceramic coating comprises a polyethylene-based film and a modified ceramic coating, wherein the modified ceramic coating comprises the following raw materials in parts by weight: 57 parts of a modified ceramic composite material, 12 parts of a binder polyvinylidene fluoride, and 2 parts of a dispersant hydroxyethyl cellulose;

[0039] The preparation method of the above lithium ion battery separator is the same as that of Example 3.

[0040] Example 5 A lithium ion battery separator with a modified ceramic coating comprises a polyethylene-based film and a modified ceramic coating, wherein the modified ceramic coating comprises the following raw materials in parts by weight: 66 parts of a modified ceramic composite material, 18 parts of a binder polyvinylidene fluoride, and 5 parts of a dispersant sodium carboxymethyl cellulose;

[0041] The preparation method of the above lithium ion battery separator is the same as that of Example 3.

[0042] Comparative Example 1 A lithium ion battery separator with a modified ceramic coating comprises a polyethylene-based film and a modified ceramic coating, wherein the modified ceramic coating comprises the following raw materials in parts by weight: 52 parts of nano-alumina, 14 parts of a binder polyvinylidene fluoride, and 3 parts of a dispersant sodium carboxymethyl cellulose;

[0043] The preparation method of the above lithium ion battery separator is the same as that of Example 3.

[0044] Comparative Example 2 A lithium ion battery separator with a modified ceramic coating comprises a polyethylene-based film and a modified ceramic coating, wherein the modified ceramic coating comprises the following raw materials in parts by weight: 40 parts of nano-alumina, 25 parts of halloysite nanotubes, 17 parts of a binder of polyvinylidene fluoride, and 3 parts of a dispersant of sodium carboxymethyl cellulose;

[0045] The preparation method of the above lithium ion battery separator is the same as that of Example 3.

[0046] Comparative Example 3 A lithium ion battery separator with a modified ceramic coating comprises a polyethylene-based film and a modified ceramic coating, wherein the modified ceramic coating comprises the following raw materials in parts by weight: 67 parts of a ceramic composite material, 20 parts of a binder polyvinylidene fluoride, and 4 parts of a dispersant sodium carboxymethyl cellulose;

[0047] The preparation method of the above lithium ion battery separator is the same as that of Example 3.

[0048] Performance Testing

[0049] The performance of the lithium ion battery separators prepared in Examples 3-5 and Comparative Examples 1-3 was tested:

[0050] (1) Air permeability test: The air permeability tester is used to test the air permeability. The results of the air permeability are expressed by the Gurley value. The smaller the Gurley value, the shorter the time for gas to pass through, and the better the air permeability of the membrane. The data results are shown in Table 1.

[0051] (2) Thermal shrinkage test: The membrane sample was cut into a size of 2 × 2 cm and heated in an electric constant temperature vacuum drying oven at 170 °C for 30 min. The dimensional change of the membrane was observed and the data results were shown in Table 1.

[0052] (3) Tensile strength test: The diaphragm samples were cut into a size of 45 × 5 mm and stretched at a rate of 5 mm / min. Each sample was grouped into 5 pieces and the average value was taken as the final result. The data results are shown in Table 1.

[0053] (4) Electrolyte wettability test: The wettability of the diaphragm to the electrolyte is tested by contact angle test and electrolyte retention rate. The contact angle test is to drop 5μL-20μL of electrolyte on the surface of the diaphragm and record the angle between the electrolyte and the diaphragm. The smaller the angle, the better the electrolyte spreads on the surface of the diaphragm and the stronger the affinity between the two. The electrolyte retention rate test is to first weigh the mass of the unsoaked diaphragm as M1, then completely immerse the diaphragm in the electrolyte for 1 hour, wipe off the excess electrolyte on the surface, weigh the mass of the diaphragm after immersion as M2, and calculate by the formula: electrolyte retention rate = (M2-M1) / M1×100%. The data results are shown in Table 1.

[0054] (5) Ionic conductivity test: Cut the diaphragm into discs with a diameter of 1.96 cm, fully soak the cut diaphragm in the electrolyte in a glove box filled with argon, take it out and place it between two stainless steel electrodes and encapsulate it in a CR2032 button battery shell. The conductivity was tested by Chenhua CHI660E electrochemical workstation, using a frequency range of 10mHz-1MHz at room temperature, and the ionic conductivity was calculated according to the formula: σ=d / (RS), where σ is the ionic conductivity, d is the thickness of the diaphragm, R is the bulk resistance of the diaphragm, and S is the effective contact area of ​​the diaphragm. The data results are shown in Table 1.

[0055] Table 1 Test results of membrane sample performance

[0056]

[0057] From the data in Table 1, it can be seen that the diaphragm prepared in Examples 3-5 of the present invention has a small contact angle, a high electrolyte holding rate, excellent electrolyte wettability, and a low thermal shrinkage rate, and has good thermal stability. At the same time, it has high air permeability and good tensile strength and ionic conductivity. Among them, the modified ceramic composite material component in Comparative Example 1 contains only nano-alumina, and its measured air permeability, thermal stability, tensile strength, electrolyte wettability and ionic conductivity are significantly reduced. In Comparative Example 2, the nano-alumina is not modified and grafted with halloysite nanotubes, and its various properties are slightly worse than those of Examples 3-5, which may be due to the reduction in performance caused by the agglomeration of nano-alumina and halloysite nanotubes. In Comparative Example 3, the modified ceramic composite material does not add a dopamine component, and its measured electrolyte wettability and ionic conductivity are slightly worse than those of Examples 3-5, which may be due to the fact that the polydopamine layer promotes the infiltration of the electrolyte inside the coating, and there is a strong polar interaction between the abundant polar functional groups in the polydopamine layer and the lithium ions.

[0058] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0059] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A lithium ion battery separator having a modified ceramic coating, characterized in that: The invention comprises a base film and a modified ceramic coating, wherein the modified ceramic coating is arranged on at least one side of the base film, and the modified ceramic coating comprises the following raw materials in parts by weight: 40 to 70 parts of a modified ceramic composite material, 5 to 20 parts of a binder, and 0.5 to 5 parts of a dispersant; the modified ceramic composite material is a modified ceramic composite material prepared by coupling agent-modified nano-alumina grafted with carboxylated halloysite nanotubes and adsorbing dopamine; The preparation method of the modified ceramic composite material comprises the following steps: A. Take anhydrous ethanol and add 10wt% citric acid solution, adjust the pH to 3-4, add γ-glycidyloxypropyltrimethoxysilane and stir for 3-5 minutes, then let it stand for 0.5-1 hour and then add nano-alumina, stir at 75-90℃ for 1-5 hours, cool to room temperature, filter, wash, dry and grind to obtain coupling agent modified nano-alumina; B. Take coupling agent-modified nano-alumina and carboxylated halloysite nanotubes, add N,N-dimethylformamide and perform ultrasonic treatment, then add triethylamine, place in an oil bath at 110-125°C and stir with nitrogen to react for 6-8h, wait for the reaction liquid to cool to room temperature, perform reduced pressure distillation, wash, filter and dry to obtain a ceramic composite material; C. The ceramic composite material is dispersed in a Tris-HCl buffer by ultrasonication, and then dopamine hydrochloride is added and stirred to react for 6 to 12 hours. After the reaction is completed, the modified ceramic composite material is obtained by centrifugation, filtration, washing and drying; The method for preparing carboxylated halloysite nanotubes in step B comprises the following steps: B1. Take γ-aminopropyltriethoxysilane, anhydrous ethanol and deionized water, stir and hydrolyze at room temperature for 1-2 hours, then add halloysite nanotubes and disperse them by ultrasonic, place under reflux reaction at 75-90°C for 12-24 hours, vacuum filter and dry after the reaction, and then use ethanol as solvent for Soxhlet extraction and dry again to obtain amination halloysite nanotubes; B2. Take the aminated halloysite nanotubes and succinic anhydride, add N,N-dimethylformamide for ultrasonic dispersion, place at 25-50°C for stirring and reacting for 12-24 hours, vacuum filter and dry after the reaction is completed, and then dry after Soxhlet extraction with ethanol as solvent to obtain carboxylated halloysite nanotubes.

2. The lithium ion battery separator with modified ceramic coating according to claim 1, characterized in that: The base film is one of a polypropylene base film, a polyethylene base film, and a polypropylene / polyethylene / polypropylene composite film; the binder is one or more combinations of polyvinyl alcohol, polyvinylidene fluoride, and polyacrylate; and the dispersant is one or more combinations of sodium carboxymethyl cellulose, polyacrylic acid, sodium polyacrylate, polyethylene glycol, and hydroxyethyl cellulose.

3. The lithium ion battery separator with modified ceramic coating according to claim 1, characterized in that: In the step A, the addition ratio of anhydrous ethanol, γ-glycidyloxypropyltrimethoxysilane and nano-alumina is 25 mL: 0.4-1.2 mL: 1-5 g.

4. The lithium ion battery separator with modified ceramic coating according to claim 1, characterized in that: In the step B, the mass ratio of the coupling agent-modified alumina to the carboxylated halloysite nanotubes is 1:0.4-0.8 g.

5. The lithium ion battery separator with modified ceramic coating according to claim 1, characterized in that: The concentration of Tris-HCl buffer in step C is 5-10 mmol / L, and the pH is 8.5; the mass ratio of the ceramic composite material to dopamine hydrochloride is 2-8:0.1-0.

5.

6. The lithium ion battery separator with modified ceramic coating according to claim 1, characterized in that: In the step B1, the addition ratio of γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and halloysite nanotubes is 8-15 mL: 90-180 mL: 25-45 mL: 2-5 g.

7. The lithium ion battery separator with modified ceramic coating according to claim 1, characterized in that: In the step B2, the mass ratio of the aminated halloysite nanotubes to succinic anhydride is 1-2.5:0.5-3.

8. The lithium ion battery separator with a modified ceramic coating according to any one of claims 1 to 7, characterized in that: The method for preparing the lithium ion battery separator comprises the following steps: (1) Weighing each raw material by weight, dissolving the binder in N-methylpyrrolidone, adding the modified ceramic composite material and the dispersant, mixing and dispersing the mixture in a ball mill, and obtaining a composite ceramic coating slurry; (2) The composite ceramic coating slurry is coated on one side of the base film, dried and rolled up to prepare a lithium-ion battery separator.